Intercom and video capture / Siti Aminah Awang and Siti Aisah Ahmad - Awang, Siti Aminah; Ahmad, Siti Aisah (2005)
The world today has demanded more than what it has ever demanded in the recent years. The race for technology and competency among human has become more intense that it has ever been. As engineering student, we should feel the intensity, the rage and challenges that await us in the future. So, to obtain that sense of keeping in flow with technology and market demands, we have to design ‘intercom and video capture’. In this project, the circuit that is used is a simple circuit. Component that we are used in this circuit are resistor, capacitor, and Ics. A detailed description of the components used to implement the circuit together with the explanation of how the circuit will operate. The proposed project will provide a better solution for our security home. These projects are inspiration for communication system and at the same time we can see that people in the video capture. The intercom system can call intercommunication system. This system can be defined as an audio frequency amplifier system that provides two¬way voice communication between two strations, which are using high frequency, and in the same structure. Each station contains a dynamic loudspeaker that also serves as microphone. The amplifier can be at station or each station may have its own amplifier. Connection between stations can be made by wire or carrier signals traveling over electric wiring in the house. It also widely used on ships and large aircraft. In other words, an option can make many business phone systems which allow you to use an abbreviated dialing sequence to react another telephone connected to the same communication system and it also called “intercom”.